Ciudad en graffitis - Jiménez, Jorge; Donas Burak, Solum (Heredia CR: EUNA, 1997)
Presenta un ensayo y una serie de fotografías relacionadas con los graffiti en la ciudad de San José.
Keywords: COSTA RICA; SAN JOSÉ (COSTA RICA); CIUDADES; GRAFFITI; ARTE; FOTOGRAFÍA